SISTEM INFORMASI PEMBELIAN DAN PENGELUARAN KAS PADA CV.ANGKASA BARU - Siswanto Siswanto; Maya Utami Dewi; Lutfi Anggraini; Agustinus Budi Santoso (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2020)
The information system for purchases and cash disbursements is one of the entire information systems. In retail sales companies need control of purchases and cash disbursements that are precise and fast. In an effort to minimize sudden out-of-stock inventory, it is necessary to secure an inventory to cope with a sudden out of stock due to delays in purchasing goods that occur at CV. New Space. This is what encourages the author to conduct research on CV. Angkasa Baru and choose the title "Purchasing Information System and Cash Distribution at CV. New Space. In writing this research systemin formation, the author uses the Microsoft Visual Basic 6.0 application, the research writing method uses the Research and Development (R&D) model, while the stages of this research model go through the stages of observation or interviews with parties related to the data required in writing this thesis, stages of designing the application system, designing specifications, validation test stages, revision of validation until the system passes. The development method used by the author is the prototype method, where the system created will be tailored to the needs of the user, if there is a change in the system it will be repaired until the user is satisfied with the system.